Analysis of teachers’ understanding of child-centered approach implementation in pre-school - Grava, Jana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The pre-school education includes teaching content and methods, which ensures development of inquisitiveness, initiative and independency. This encourages child to explore skills, solve tasks and make decisions independently. That makes up the ability to think flexibly and be able to use knowledge in different life situations. Such conditions in education meet the guidelines of child-centered pedagogical approaches. Though the majority of preschools present themselves as supporting the child-centered approach, the conclusion is that the term "child-centered approach" is variously understood and interpreted. It makes variety of assumptions about early childhood education process. This article explores teachers' understanding of the factors which determines the childcentered approach, emphasizing the need to respect the interests of a child, to acquire the skills to select and solve problems. Basically, it is provided by adult and child interaction, based on a meaningful and respectful cooperation as a result of developing a child's selfexperience.